EDUKASI VIDEO ANIMASI VAKSINASI HUMAN PAPILLOMAVIRUS MENINGKATKAN PENGETAHUAN DAN SIKAP SISWI SEKOLAH MENENGAH PERTAMA - Niken Lestari; Irma Nurbaeti; Maulina Handayani; Ita Yuanita; Muhammad G.A. Putra; Rahma Dwi Syukrini; Birrul Qodriyyah (Jurnal AbdiMas Nusa Mandiri, 2026)
Cervical cancer is one of the major global health problems caused by Human Papillomavirus (HPV) infection. One of the most effective preventive measures is HPV vaccination. To support this effort, health education is needed to improve female students' understanding of the importance of HPV vaccination. This community service activity aimed to analyze the effect of animated video-based health education on improving the knowledge and attitudes of female junior high school students regarding HPV vaccination. Health education was delivered using animated videos, and participants' knowledge and attitudes were assessed before and after the intervention. The activity involved 92 female junior high school students in grades 7–9 in South Jakarta and was conducted in January 2026. Univariate analysis was performed based on the total knowledge and attitude scores, while bivariate analysis was conducted using the Wilcoxon test to assess differences before and after the intervention. The mean knowledge score before the intervention was 13.72 (SD = 3.106; median = 14.00), which increased to 17.05 (SD = 2.333) after the intervention. The mean attitude score increased from 44.43 (SD = 5.474) to 49.64 (SD = 5.980). The Wilcoxon test showed a statistically significant difference between the pre-test and post-test scores (p = 0.001) for both knowledge and attitudes. Animated video-based health education was proven to be effective in improving knowledge and attitudes toward HPV vaccination and can be used as an alternative educational medium.